1969
DOI: 10.1128/jb.100.2.760-762.1969
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Deoxyribonuclease Production by Yeasts

Abstract: A total of 20 genera of yeasts and yeastlike organisms were tested for their ability to produce an extracellular deoxyribonuclease. Results indicate that ability to produce the enzyme appears to be a specific characteristic of the three genera Rhodotorula, Cryptococcus, and Tremella. A single strain of Endomycopsis fibuligera was also shown to be positive for the enzyme. In comparing the ability of the organisms to excrete extracellular deoxyribonuclease with their ability to produce urease, a surprisingly clo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

1971
1971
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(15 citation statements)
references
References 14 publications
0
14
0
1
Order By: Relevance
“…The differentiation of Serratia from Enterobacter species (9) relies in part on detection of the enzyme. Additionally, the ability to produce DNase is indicative of several yeast genera (2).…”
mentioning
confidence: 99%
“…The differentiation of Serratia from Enterobacter species (9) relies in part on detection of the enzyme. Additionally, the ability to produce DNase is indicative of several yeast genera (2).…”
mentioning
confidence: 99%
“…Our results support study who reported that both species produce extracellular DNase, but clinical isolates of C. neoformans produce significantly more extracellular DNase than environmental isolates 20 . Extracellular DNase activity exhibits an essential role of in the taxonomic and phylogenetic studies of the genus Cryptococcus 11 .…”
Section: Resultsmentioning
confidence: 99%
“…Then the inoculated plates were flooded with 1 N hydrochloric acid. Yeasts that depolymerized DNA contained in the medium exhibited clear zones surrounding the colonies, whereas those organisms which exhibited no extracellular DNase activity showed only the opaque background of precipitated DNA 20,11 .…”
Section: Determination Of Dnase Productionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the environment, urease probably assists C. neoformans in converting urea into a usable nitrogen source in pigeon guano (Cox et al, 2000). DNAse production is found in bacterial pathogens (Sanchez and Colom, 2010), as well as non-pathogenic Cryptococcus, Rhodotorula and Tremella (Cazin et al, 1969). Interestingly, higher activity (and greater diversity) of DNAse was observed from clinical C. neoformans strains compared with environmental strains (Sanchez and Colom, 2010).…”
Section: Vertebrate Modelsmentioning
confidence: 99%